2011
DOI: 10.1080/00032711003789967
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Calibration of Near Infrared Spectroscopy in the Presence of Light Scattering Effect: A Comparative Study

Abstract: Abstract:When analyzing heterogeneous samples using spectroscopy, the light scattering effect introduces non-linearity into the measurements and deteriorates the prediction accuracy of conventional linear models. This paper compares the prediction performance of two categories of chemometric methods: pre-processing techniques to remove the non-linearity, and non-linear calibration techniques to directly model the non-linearity. A rigorous statistical procedure is adopted to ensure reliable comparison. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 30 publications
(6 reference statements)
0
20
0
Order By: Relevance
“…Prior to developing the non-linear calibration models (ANN and GPR), PLS is first applied to reduce the dimension of the data, which is a common method used to reduce the computational cost of parameter estimation in non-linear models [34]. Conceptually, non-linear models are capable of direct modelling of the non-linearity; we also empirically observed that pre-processing methods, which aim to remove the non-linearity of the data, do not improve the non-linear calibration models [25]. As a result, these scattering correction techniques are not used for nonlinear models.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Prior to developing the non-linear calibration models (ANN and GPR), PLS is first applied to reduce the dimension of the data, which is a common method used to reduce the computational cost of parameter estimation in non-linear models [34]. Conceptually, non-linear models are capable of direct modelling of the non-linearity; we also empirically observed that pre-processing methods, which aim to remove the non-linearity of the data, do not improve the non-linear calibration models [25]. As a result, these scattering correction techniques are not used for nonlinear models.…”
Section: Resultsmentioning
confidence: 97%
“…wavelength-dependent multiplicative effect due to disturbances). In the literature, non-linear calibration has shown comparable prediction performance with pre-processing techniques [25].…”
Section: Non-linear Calibration Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ANN on the other hand is a flexible mathematical structure capable of identifying complex Developments in Near-Infrared Spectroscopynonlinear interactions between input and output data sets. This method is reported to be useful and efficient, especially in problems for which the characteristics are difficult to describe using physical equations [53]. The ANN model has been shown to perform better than linear models [54].…”
Section: Nonlinear Calibration Models For Near-infrared Spectroscopymentioning
confidence: 99%
“…Second, the meta-model can have different forms, such as polynomial functions, neural networks, and Gaussian process regression (GPR, also known as kriging) (Palmer & Realff 2002, Chen et al 2006. Of particular focus in this work is GPR, for its reliable prediction results when compared with alternative methods (O'Hagan 2006, Wang et al 2011.…”
Section: Introductionmentioning
confidence: 99%